MR imaging of optic nerve lesions: value of gadopentetate dimeglumine and fat-suppression technique. - Hendrix, L E; Kneeland, J B; Haughton, V M; Daniels, D L; Szumowski, J; Williams, A L; Mark, L P; Czervionke, L F (American Journal of Neuroradiology, 1990)
Eleven patients with known or suspected optic nerve lesions and eight normal subjects were examined with spin-echo technique at 1.5 T with unenhanced T1-weighted imaging, IV gadopentetate-dimeglumine-enhanced T1-weighted imaging, and enhanced T1-weighted imaging with fat suppression. Two pathologically proved and four presumed optic nerve meningiomas demonstrated significant enhancement and were best seen with the fat-suppression technique. None of the three presumed optic nerve gliomas nor the optic nerves of normal subjects demonstrated qualitative enhancement. We conclude that the use of a fat-suppression technique with gadopentetate dimeglumine enhancement improves delineation of enhancing optic nerve lesions. This technique should be useful for evaluating other anatomic regions where enhancing tissue marginates fat.